O zespole doradców socjologicznych Obywatelskiego Klubu Parlamentarnego - Post, Barbara (Studia Polityczne, 2018)
The article contains the analysis of narratives collected in autumn 2017 during in-depth interviews with the participants of the sociological think tank of the Civic Parliamentary Club (OKP) who wanted and were freely able to participate in them. The collected material is therefore of qualitative character and the narratives analysed make it possible to show how members of the think tank perceived their role, why they decided to perform it and what their relations with politicians they advised were. Expert opinions prepared by the sociological think tank are also part of the analysis, constituting an interesting testimony of social attitudes and processes taking place in the first period of Polish transformation.